(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
As being exposed to water that exists on asphalt road, HMA that is created by utilizing a certain resources may require to be made strong due to the capability of that water to stop the covering to be attached to the aggregate, consequently, asphalt road layers will not be held jointly, this will have a negative influence on the asphalt that will be damaged quickly. Such phenomenon is known as "the erosion", which requires to be dealt with by, for example, improving asphalt layers by means of specific resources that assist in existence of water. Different ways in this work are employed to calculate the strength of various mixes via using used aggregate that is exposed to saturation times, similarly, the importance of exploiting the anti-stripping as chemical addition is determined. Three kinds of HMA were exposed in the current study, 60% of the first kind were made of used aggregate taking from crushed pavement, and 60% of the second kind were taking from using aggregate that is part of concrete mix, while the third mixture has 10% of wax used as an addition by pavement weight. These mixtures were soaked in water bath of 25o C for various intervals of time that are (3, 7, 15, 28) days. Many investigations examinations had been as well executed, and then the outcomes were contrasted against standard pavement blend subjected to similar circumstances. Number of examinations were adopted in this study, these are (Marshall Stability and flow), mass thickness, roundabout elasticity, compressive quality, affectability to temperature, flexible modulus. The study achieved a good success as it makes important outcomes, the enhanced pavement showed strength against moisture damage while taking advantage of used aggregate of preceding blends, on other hand, the wax has affective role in raising these strengths in addition to develop the characteristics of HMA.